Stress, family support, and spiritual adaptation as predictors of the quality of life of pregnant women during the covid-19 pandemic - Putri Dafriani; Ratna Indah Sari Dewi; Eliza Trisnadewi; Harinal Afri Resta; Roza Marlinda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Objective: To determine the predictor factors of the quality of life of pregnant women during the COVID-19 pandemic. The COVID-19 pandemic affects the quality of life of pregnant women. Quality of life is determined by stress, family support and spiritual adaptation. Methods: This study used a cross-sectional study design. A total of 300 pregnant women were recruited using proportional sampling methods. The study participants completed questionnaire of World Health Organization Quality of Life (WHOQOL-BREF) 2004 to identify their quality of life, Perceived Stress Scale (PSS) to measure perceived stress, Perceived Social Support Family (PSS-Fa) to assess their family support, and Spiritual Perspective Scale (SPS) to determine their spiritual adaptation, respectively. Data were analysed statistically using Multiple regression and Pearson correlation. Result: More than half of the participants reported Good Quality of Life (QoL) (50.3%), and faced stress (62,3%), high family support (53%), high spiritual adaptation (61,3%). Stress, family support, and spiritual adaptation were found to be statistically significantly related to Quality of Life (QoL) (p-value1,2,3=0.000); r1=0.472, r2=0.446, and r3=0.605, respectively). Conclusion: Maintain a good quality of life of pregnant women is very important and it is affected by stress, family support and spiritual adaptation. Spiritual adaptation found to be the most affecting predictors of QoL among pregnant mother during COVID-19 pandemic. Abstrak: Tujuan: Untuk mengetahui faktor prediktor kualitas hidup ibu hamil di masa pandemi COVID-19. Pandemi COVID-19 mempengaruhi kualitas hidup ibu hamil. Kualitas hidup ditentukan oleh stres, dukungan keluarga dan adaptasi spiritual. Metode: Penelitian ini menggunakan desain cross sectional study. Sebanyak 300 ibu hamil direkrut menggunakan metode proporsional sampling. Peserta studi menyelesaikan kuesioner Kualitas Hidup Organisasi Kesehatan Dunia (WHOQOL-BREF) 2004 untuk mengidentifikasi kualitas hidup mereka, Perceived Stress Scale (PSS) untuk mengukur stres yang dirasakan, Perceived Social Support Family (PSS-Fa) untuk menilai dukungan keluarga mereka, dan Spiritual Perspective Scale (SPS) untuk menentukan adaptasi spiritual mereka, masing-masing. Data dianalisis secara statistik menggunakan regresi berganda dan korelasi Pearson. Hasil: Lebih dari setengah peserta melaporkan Kualitas Hidup yang Baik (QoL) (50,3%), dan menghadapi stres (62,3%), dukungan keluarga yang tinggi (53%), adaptasi spiritual yang tinggi (61,3%). Stres, dukungan keluarga, dan adaptasi spiritual ditemukan secara statistik terkait secara signifikan dengan Kualitas Hidup (QoL) (p-value1,2,3=0,000); r1=0,472, r2=0,446, dan r3=0,605, masing-masing). Kesimpulan: Menjaga kualitas hidup ibu hamil yang baik sangat penting dan dipengaruhi oleh stres, dukungan keluarga dan adaptasi spiritual.  Adaptasi spiritual ditemukan sebagai prediktor QoL yang paling mempengaruhi di antara ibu hamil selama pandemi COVID-19.